Jaws. 2 [videorecording (Blu-Ray)] - Gottlieb, Carl; Sackler, Howard; Scheider, Roy; Gary, Lorraine, 1937-; Hamilton, Murray (Universal Pictures Home Entertainment, 2016)
Four years after the great white shark terrorized the small resort of Amity, unsuspecting vacationers begin disappearing in an all-too-familiar fashion. Police Chief Brody finds himself in a race against time when a new shark attacks ten sailboats manned by teenagers, including his own two sons. The same heart-stopping suspense and gripping adventure that enthralled movie audiences throughout the world in Jaws returns in this worthy sequel to the original motion picture classic.